The last frontier of natural guide star adaptive optics - Pinna, Enrico (Il Colle di Galileo, 2021)
Adaptive optics is finding increasingly relevant applications in ground-based optical and infrared astronomy and will be the key technique for the next generation of telescopes. The technology group at INAF-Osservatorio Astrofisico di Arcetri has recently installed a frontier instrument on the Large Binocular Telescope and has obtained the first astrophysical data confirming its innovative performance.